1978
DOI: 10.1029/gl005i012p01047
|View full text |Cite
|
Sign up to set email alerts
|

Electric fields and conductivity in the nighttime E‐region: A new magnetosphere‐ionosphere‐atmosphere coupling effect

Abstract: Calculations have been made of the effects of intense poleward‐directed electric fields upon the nighttime ionospheric E‐region. The results show the Pedersen and Hall conductivities are substantially changed, thereby decreasing the ionospheric electrical load seen by magnetospheric sources. It appears that relatively large electric fields can exist in the absence of accompanying large field‐aligned currents, as long as the underlying ionosphere remains in darkness and/or energetic particle precipitation is ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 4 publications
3
51
0
Order By: Relevance
“…The cause and effect may be the opposite, as discussed above, with downward current systems associated with magnetospheric processes causing low density and thus low conductance regions in the ionosphere. This phenomenon, "E-region cavity formation", has been modeled by Banks and Yasuhara (1978); Doe et al (1995); Karlsson and Marklund (1998), and cavity formation against a solar EUV produced E-region background in the dayside cusp region was observed by Nilsson et al (1998). Such cavity formation may in turn contribute to further ionospheric feedback, as modeled by Streltsov and Lotko (2002).…”
Section: Introductionmentioning
confidence: 99%
“…The cause and effect may be the opposite, as discussed above, with downward current systems associated with magnetospheric processes causing low density and thus low conductance regions in the ionosphere. This phenomenon, "E-region cavity formation", has been modeled by Banks and Yasuhara (1978); Doe et al (1995); Karlsson and Marklund (1998), and cavity formation against a solar EUV produced E-region background in the dayside cusp region was observed by Nilsson et al (1998). Such cavity formation may in turn contribute to further ionospheric feedback, as modeled by Streltsov and Lotko (2002).…”
Section: Introductionmentioning
confidence: 99%
“…The larger scale size is the ~4.5° latitudinal width of the SAPS structure and the smaller one is that of the plasma irregularity structures. The coincidental formation of plasma density troughs and SAPS structures was predicted based on theoretical considerations by Schunk et al [1976] and Banks and Yasuhara [1978]. They argued that intense electric fields in the subauroral ionosphere would lead to the formation of deep troughs through a combination of plasma outflow and enhanced recombination stemming from the charge exchange reaction O^ + N2 -> NO^ + N whose rate k^j^ increases in the convecting/ heated plasma.…”
Section: Source For Observed Plasma Irregularitiesmentioning
confidence: 99%
“…Banks and Yasuhara (1978) reported that large poleward electric fields have the effect of substantially reducing the Pedersen and Hall conductivities on the equatorward side of this region. This effect, in turn, influences the spatial distribution of field-aligned currents (FAC), and reduces the magnitude of current needed to support the imposed electric field.…”
Section: Introductionmentioning
confidence: 99%